Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/s12931-014-0106-1
|View full text |Cite
|
Sign up to set email alerts
|

PlGF mediates neutrophil elastase-induced airway epithelial cell apoptosis and emphysema

Abstract: BackgroundChronic pulmonary obstructive disease (COPD) has become the fourth leading cause of death worldwide. Cigarette smoking induces neutrophil elastase (NE) and contributes to COPD, but the detailed mechanisms involved are not fully established. In an animal model of pulmonary emphysema, there are increased expressions of placenta growth factor (PlGF) and lung epithelial (LE) cell apoptosis. This study hypothesized that excessive NE may up-regulate PlGF and that PlGF-induced LE apoptosis mediates the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
(51 reference statements)
0
17
0
1
Order By: Relevance
“…Later stages in HPS development in our study were characterized by pulmonary neutrophil infiltration and elevated levels of NE in BALF. Other studies have described a role for elastase and PlGF in inducing AT2 cell death during pulmonary emphysema, and a recent report demonstrated AT2 cell dysfunction after CBDL in rats . In line with this, we have shown that αPlGF attenuates the AT2 cell proinflammatory and caspase 3/7 response to LPS in vitro .…”
Section: Discussionmentioning
confidence: 58%
“…Later stages in HPS development in our study were characterized by pulmonary neutrophil infiltration and elevated levels of NE in BALF. Other studies have described a role for elastase and PlGF in inducing AT2 cell death during pulmonary emphysema, and a recent report demonstrated AT2 cell dysfunction after CBDL in rats . In line with this, we have shown that αPlGF attenuates the AT2 cell proinflammatory and caspase 3/7 response to LPS in vitro .…”
Section: Discussionmentioning
confidence: 58%
“…For example, one study found that PlGF levels significantly elevate in serum and BALF of COPD patients and negatively relate with forced expiratory volume in 1 sec 13. In a separate study from the same group, it was discussed that the neutrophil’s elastic protease (pig pancreas) could increase the expression of PlGF and induce lung epithelial cell apoptosis 27. However, neither study addressed whether CS could directly stimulate PlGF overproduction in human airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…A conserved Egr-1 binding site is found near the PlGF promoters of mouse and human genomes 3234. Hou et al27 reported that neutrophil elastase induced PlGF expression through promoting Egr-1 transcriptional activity. Our results demonstrate that CSE can induce Egr-1 expression, nuclear translocation and transcriptional activity in 16-HBE cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the JNK inhibitor, SP600125, partly prevented bleomycin-induced hydroxyproline and a smooth muscle actin levels in the lung tissue of rats, and thalidomide, an immunomodulatory drug able to suppress the generation of TNF-a, prevented the induction of JNK phosphorylation and hydroxyproline and a smooth muscle actin levels even more (34). Furthermore, neutrophil elastase-instilled mice showed emphysema and lung epithelial cell apoptosis, which was JNK and protein kinase C signaling dependent (35).…”
Section: Discussionmentioning
confidence: 95%